Psychosocial care in the process of Venezuelan Interiorization: Experience report (Research, Society and Development, 2022)
The Multiprofessional Residency in Health acts as a strategy in health care for vulnerable populations, such as refugees. There has been an increase in the number of requests for refuges, especially due to the Venezuelan migratory wave. This article systematizes the experience of Mental Health residents with health care for Venezuelans welcomed by the Interiorization Process. This is an experience report. There is a need to look at mental health in situations of forced displacement, building autonomy and citizenship. Municipal resources were mapped and the need for networking was identified, especially in mental health. Anxieties were noted in Venezuelans due to family distance, lack of knowledge of the flow of access to Brazilian services, labor issues, housing and mistrust in peers given extreme situations experienced in Venezuela, in the migratory crossing and in Brazil. The need for permanent education of professionals, intersectoral articulation, preparation of a bilingual booklet, and spaces for socialization, leisure and culture, essential for mental health care, was pointed out.